2021
DOI: 10.31235/osf.io/qu326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online Learning amid COVID-19 Pandemic: A Case Study of Vocabulary Learning Strategies

Abstract: The outbreak of Coronavirus disease (COVID-19) has led countries to implement measures to prevent its spread. One of these measures included shutting down schools and universities. Consequently, the teaching, learning and assessment processes were entirely shifted from face-to-face to online. The current study aimed to investigate online vocabulary learning strategies (VLSs) amid COVID-19 pandemic used by Saudi EFL students. It attempted to find out the online strategies Saudi EFL astudents use to get the mean… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…Resulta interesante que, en este estudio, Shamsan et al (2021) reportan poco sobre EAV mediadas por la tecnología. De igual manera, llama la atención un nuevo estudio que se enfocó en recabar información sobre el uso de los diccionarios electrónicos como EAV.…”
Section: Revisión De La Literaturaunclassified
See 3 more Smart Citations
“…Resulta interesante que, en este estudio, Shamsan et al (2021) reportan poco sobre EAV mediadas por la tecnología. De igual manera, llama la atención un nuevo estudio que se enfocó en recabar información sobre el uso de los diccionarios electrónicos como EAV.…”
Section: Revisión De La Literaturaunclassified
“…De hecho, la EAV de uso de diccionario y otras fuentes de consulta emergió como una de las más frecuentes entre las 13 categorías. Este resultado coincide con los hallazgos reportados por Asgari y Mustapha (2011), Saengpakdeejit (2014), Rachmawati (2017), Lestari y Puspitasari (2021), Shamsan et al (2021) y Alamri y Hakami (2022).…”
Section: Discusión Y Conclusionesunclassified
See 2 more Smart Citations
“…Moreover, 15 of the 20 participants claimed they use English-language media (songs, TV shows, movies, and video games) to learn new vocabulary. Shamsan et al (2021) investigated the preferred VLSs by two groups of learners during online learning due to Covid-19 restrictions. The result showed that non-English major learners reported that inferencing the meaning from the context was their favourite strategy, while English major learners' common strategy was to look up new words in a bilingual dictionary.…”
Section: Questions Of the Studymentioning
confidence: 99%